Tradução e estudo de excertos acerca do conceito de Geltung na lógica (1874) de Hermann Lotze - Macedo, Lucas Kattah (2015)
This text aims to present a translation of the Chapter "The World of Ideas" of Hermann Lotze's Logic (1874), along with the translation of other extracts and with an introductory study for their understanding. Realize the importance of such work to the extent that we can grasp the concept of the philosopher's own logic, characterized by a theory of validity and an anti-psychologism